2014
DOI: 10.1016/j.ijid.2014.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackieviruses in Ontario, January 2005 to December 2011

Abstract: The increase in enterovirus meningitis in Ontario in 2010 was likely due to an increase in A9 circulation. A9 was most commonly identified among children; however A9 may cause severe illness in both children and adults. Monitoring the circulation and epidemiology of enteroviruses can inform clinicians about circulating pathogens to optimize clinical testing and antibiotic use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Consequently, the control group had to be enrolled in another country because we were logistically unable to enrol a reasonable number of healthy young children in our institution or nearby hospitals. However, both Canada and Switzerland have a continental climate with a seasonal circulation of HEV and HPeV,7 8 17 22 37 38 whereas AdV and HHV-6 circulate throughout the year 9 10. Also, the enrolment breakdown according to seasons differed between study patients and controls, with most controls enrolled during the autumn; however, a subanalysis including only patients included in the autumn confirmed that viraemia was still significantly more frequent in study patients.…”
Section: Discussionmentioning
confidence: 94%
“…Consequently, the control group had to be enrolled in another country because we were logistically unable to enrol a reasonable number of healthy young children in our institution or nearby hospitals. However, both Canada and Switzerland have a continental climate with a seasonal circulation of HEV and HPeV,7 8 17 22 37 38 whereas AdV and HHV-6 circulate throughout the year 9 10. Also, the enrolment breakdown according to seasons differed between study patients and controls, with most controls enrolled during the autumn; however, a subanalysis including only patients included in the autumn confirmed that viraemia was still significantly more frequent in study patients.…”
Section: Discussionmentioning
confidence: 94%
“…There are numerous reports of CVA9 as a significant causal agent of aseptic meningitis from around the world, including Japan (1961) [32], Northern Ireland (1970) [33], Poland (1974) [34, 35], Cuba (1990–1991) [36], Argentina (2007–2008) [37], Switzerland [38], Canada (2010) [39, 40], China (2006–2012) [41] as well South Africa [14]. Consistent with our study, the majority of cases occurred in children under 10 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of active (stool samples for all cases of acute flaccid paralysis) and passive (EV genotyping) samples are used by the NML. Between Jaunary 1, 2005 and December 31, 2011, 0.9% of 941 specimens positive for EV submitted to the Public Health Ontario Laboratory were positive for EV-A71 according to viral culture ( 3 ). Another 20 cases of EV-A71 in one tertiary care pediatric centre were reported in 1998 ( 4 ).…”
Section: Discussionmentioning
confidence: 99%